Ultrasound assessment of gastric content in patients undergoing laparoscopic cholecystectomy after preoperative oral carbohydrates: a prospective, randomized controlled, double-blind study - Ge, Yali; Shen, Dejuan; Ding, Yinyin; Wu, Keting; Zhang, Yang (Frontiers in Surgery, 2023)
Background To evaluate the gastric volume and nature after drinking preoperative oral carbohydrates in patients undergoing laparoscopic cholecystectomy via ultrasonography. Methods One hundred patients who had been scheduled for elective laparoscopic cholecystectomy were enrolled and randomized into the traditional fasting group (Control group, n = 50) and the carbohydrate group (CHO group, n = 50). Patients in the Control group fasted solids and drink from midnight, the day before surgery. Patients in the CHO group drank 800 ml and 400 ml of oral carbohydrates 11 and 3 h before surgery, respectively. At 2 h after oral carbohydrates (T1), all patients underwent an ultrasound examination of residual gastric contents; if the patients had a full stomach, the assessment was performed again 1 h later (T2). A stomach containing solid contents or >1.5 ml/kg of liquid was considered “full”. The primary outcome was full stomach incidences at the above time points. The secondary outcomes included gastric antral CSA in the right lateral decubitus (RLD) and semi-sitting positions, as well as gastric volume (GV), GV per weight (GV/kg), and Perla's grade at T1. Results Compared with the Control group, the incidence of entire stomach was significantly high in the CHO group 2 h after oral carbohydrates. At the T1 time point, 6 patients (13.3%) in the Control group and 14 patients (30.4%) in the CHO group presented with a full stomach [95% confidence interval (CI), (0.96–5.41), P = 0.049]. At T2, 3 patients (6.7%) in the Control group and 4 patients (8.7%) in the CHO group had a full stomach, with no marked differences between the two groups [95% CI, (0.31–5.50), P = 0.716]. Compared with the Control group, CSA in the semi-sitting and RLD positions, GV and GV/W were significantly high in the CHO group at T1 (P < 0.05). The median (interquartile range) of the Perlas grade was 1 (0–1) in the Control group and 1(1–1.25) in the CHO group (P = 0.004). Conclusion Cholecystectomy patients experience a 2 h delay in gastric emptying after receiving preoperative carbohydrates. In LC patients, the fasting window for oral carbohydrates before surgery should be adequately prolonged. Clinical Trail registration Chinese Clinical Trail Registry, No: ChiCTR2200055245.